⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ x + y + z = − 1 x 2 + y 2 + z 2 = − 2 x 3 + y 3 + z 3 = − 3 x 4 + y 4 + z 4 = b a
In the last equation above, a and b are coprime integers, enter ∣ a ∣ + ∣ b ∣ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice one! I didn't know about Netwon's sums.
Log in to reply
It is the standard way of solving this type of problems.
Last line - change P 3 to P 4 , and fourth line change S 2 to S 3 .
We can start by squaring equation #1:
( x + y + z ) 2 = ( − 1 ) 2
x 2 + y 2 + z 2 + 2 x y + 2 x z + 2 y z = 1
We recognize x 2 + y 2 + z 2 = − 2 so:
⟹ 2 x y + 2 x z + 2 y z = 3
x y + x z + y z = 2 3 (a)
Now, if we cube equation #1:
( x + y + z ) 3 = ( − 1 ) 3
x 3 + y 3 + z 3 + 3 x 2 y + 3 x 2 z + 3 x y 2 + 3 x z 2 + 3 y 2 z + 3 y z 2 + 6 x y z = − 1
⟹ x 2 y + x 2 z + x y 2 + x z 2 + y 2 z + y z 2 + 2 x y z = 3 2 (b)
Observe that if we multiply (a) by x , y and z :
x 2 y + x 2 z + x y z = 2 3 x
x y 2 + x y z + y 2 z = 2 3 y
x y z + x z 2 + y z 2 = 2 3 z
And add them we get (b) with an extra x y z term, so:
⟹ x 2 y + x 2 z + x y 2 + x z 2 + y 2 z + y z 2 + 2 x y z = 2 3 ( x + y + z ) − x y z
3 2 = − 2 3 − x y z
⟹ x y z = − 6 1 3
We can also square equation #2 to get:
( x 2 + y 2 + z 2 ) 2 = x 4 + y 4 + z 4 + 2 x 2 y 2 + 2 x 2 z 2 + 2 y 2 z 2 ≡ 4
To find out what the red terms are let us square equation (a) :
( x y + x z + y z ) 2 = x 2 y 2 + x 2 z 2 + y 2 z 2 + 2 x 2 y z + 2 x y 2 z + 2 x y z 2 ≡ 4 9
We can factor 2 x y z = − 3 1 3 from the green terms:
⟹ − 3 1 3 ( x + y + z ) = 3 1 3
And we find out that x 2 y 2 + x 2 z 2 + y 2 z 2 = − 1 2 2 5 . Finally:
x 4 + y 4 + z 4 + 2 x 2 y 2 + 2 x 2 z 2 + 2 y 2 z 2 = 4
x 4 + y 4 + z 4 − 6 2 5 = 4
⟹ x 4 + y 4 + z 4 = 6 4 9
The final answer is 4 9 + 6 = 5 5
Problem Loading...
Note Loading...
Set Loading...
Let P n = x n + y n + z n , where n is a positive integer; S 1 = x + y + z = − 1 ; S 2 = x y + y z + z x , and S 3 = x y z . By Newton's sums or identities , we have:
P 1 P 2 P 3 P 4 = S 1 = − 1 = S 1 P 1 − 2 S 2 = − 1 ( − 1 ) − 2 S 2 = − 2 = S 1 P 2 − S 2 P 1 + 3 S 3 = − 1 ( − 2 ) − 2 3 ( − 1 ) + 3 S 3 = − 3 = S 1 P 3 − S 2 P 2 + S 3 P 1 = − 1 ( − 3 ) − 2 3 ( − 2 ) − 6 1 3 ( − 1 ) = 6 4 9 ⟹ S 2 = 2 3 ⟹ S 3 = − 2 1 3
Therefore, ∣ a ∣ + ∣ b ∣ = 4 9 + 6 = 5 5 .